Knowledge and Attitude Regarding Infection Control and Standard Precautions among Healthcare Workers of Rural Nepal - Rajbhandari, Ajay Kumar; Sagtani, Reshu Agrawal; Thapa, Bijay; Adhikari, Puspanjali (Birat Journal of Health Sciences, 2018)
Introduction: A healthcare associated infection (HCAI) during patient care is an emerging challenge to healthcare service delivery. Transmission of most of these HCAIs can be prevented through application of standard precautions which are a set of infection control practices followed during patient care, whether or not they appear infectious or symptomatic. Objective: This study aims to assess the existing knowledge and attitude on infection control and standard precautions among healthcare personnel working in peripheral healthcare settings of Nepal. Methodology: It was a cross-sectional study and included nine different health facilities in Makwanpur district. Knowledge and attitude regarding infection control and standard precautions were assessed with the help of a self-administered questionnaire on a pre-determined scale. The results are presented as frequency distribution table and valid proportions. Results: In the study, 91.9% of the HCWs agreed that HCAI is caused by micro-organisms that can be transmitted between patients while 51.5% of them disagreed that HCAI can be caused by micro-organisms carried on the hands of healthcare workers. Majority (98.6%) of the HCWs believed that the use of gloves, mask and apron reduces the risk of HCAI whereas 13.5% of HCWs disagreed that gloves should be changed between the examination of different patients. Although 97% of the HCWs agreed that hand should be washed before and after examining the patient, 17.6% of them informed that they do not always wash their hands before and after examining a patient. Conclusion: Irrespective of limited availability of infection control guidelines, it was found that the knowledge on HCAI control was good and majority of the respondents showed favorable attitude towards infection control and standard precautions. BJHS 2018;3(2)6: 453-457.